Impact of Underlying Insulators on the Crystallinity and Antisite Defect Formation in PVD-MoS2 Films - Matsunaga, Naoki; Imai, Shinya; Shirokura, Takanori; Mochizuki, Yasuhide; Kuwahata, Kazuaki; Tsutsui, Kazuo; Kakushima, Kuniyuki; Wakabayashi, Hitoshi (IEEE journal of the Electron Devices Society, 2025)
The effect of different underlying insulators on molybdenum disulfide (MoS2) films deposited using sputtering, which is a physical vapor deposition (PVD) method, was studied. The study reveals that the underlying insulator strongly affects the properties of the deposited PVD-MoS2 films. First, the results suggested the formation of Mo antisites during sputtering deposition, which weaken the Mo-S bonds in the MoS2 film and enhances its carrier density. Second, the crystallinity of the MoS2 films was evaluated on the basis of Raman intensity and fast Fourier transform (FFT) analysises of cross-sectional transmission electron microscopy (TEM) images. Among the samples investigated, MoS2 deposited onto atomic layer deposition (ALD)-SiO2 exhibited the highest crystallinity. These findings highlight the critical role of the underlying insulator in optimizing PVD-MoS2 films for future applications in three-dimensionally stacked field-effect transistors.